A Swollen Hand With Blisters. Issue 6 (June 2015) - Rios-Alba, Tonatiuh; Ahn, James
<x xml:space="preserve">Abstract</x> Abstract The accurate identification of compartment syndrome in the emergency department is essential to timely treatment and prevention of long-term sequela. Recognizing compartment syndrome is not straightforward, especially in the pediatric population. In addition to communication barriers that exist with children, the classic signs of pain, pallor, paresthesia, paralysis, and pulselessness are not always present, making its diagnosis a challenge. We report a case of a child with compartment syndrome to the left hand due to compression from an ACE wrap. The existing literature on compartment syndrome in children is reviewed.